Current Insights Into Oligodendrocyte Metabolism and Its Power to Sculpt the Myelin Landscape - Narine, Mohanlall; Colognato, Holly (Frontiers in Cellular Neuroscience, 2022)
Once believed to be part of the nervenkitt or ‘nerve glue’ network in the central nervous system (CNS), oligodendroglial cells now have established roles in key neurological functions such as myelination, neuroprotection, and motor learning. More recently, oligodendroglia has become the subject of intense investigations aimed at understanding the contributions of its energetics to CNS physiology and pathology. In this review, we discuss the current understanding of oligodendroglial metabolism in regulating key stages of oligodendroglial development and health, its role in providing energy to neighboring cells such as neurons, as well as how alterations in oligodendroglial bioenergetics contribute to disease states. Importantly, we highlight how certain inputs can regulate oligodendroglial metabolism, including extrinsic and intrinsic mediators of cellular signaling, pharmacological compounds, and even dietary interventions. Lastly, we discuss emerging studies aimed at discovering the therapeutic potential of targeting components within oligodendroglial bioenergetic pathways.